The Gender Gap in Life Expectancy in Urban and Rural China, 2013-2018 - Jinjing Wu; Samir KC; Samir KC; Marc Luy (Frontiers Media S.A., 2022)
BackgroundGender differences in mortality are embedded within mortality transitions. Rural residents generally lag behind their urban counterparts in the transitions. The study objective is to identify major causes of death that drive gender differences in mortality in urban and rural China.MethodsWe use age-, gender-, urban-rural- and cause-specific mortality data (2013-2018) derived from the national mortality surveillance system that covered about 24% of the Chinese population. We apply Arriaga's method to decompose age- and cause-specific contributions to the gender gap in life expectancy at birth. Analyses are stratified by urban-rural residence.ResultsWomen had a higher life expectancy at birth than men in both urban and rural areas. Cancers, cardiovascular disease, external causes, and respiratory disease accounted for more than 90% of the gender gap in both areas during 2013-2018. In urban areas, the gender gap decreased from 5.17 years in 2013-2015 to 4.98 years in 2016-2018. In rural areas, the gender gap stayed rather constant (2013-2015: 5.68 years; 2016-2018: 5.65 years). Traffic accidents, among external causes, contributed the most to decreasing the gender gap (urban: −0.07 years; rural: −0.10 years), especially in the 0-44 age group. However, the decrease in the gender gap was counteracted by an increase in the gender gap attributable to ischemic heart disease (urban: +0.05 years; rural: +0.08 years) and lung cancer (urban: +0.02 years; rural: +0.05 years) in older age groups. The gender gap attributable either to cerebrovascular disease or to chronic lower respiratory disease decreased in urban areas but increased in rural areas.ConclusionsThe urban-rural variations in the cause-specific contributions to the gender gap in China suggest the necessity of implementing urban-rural-specific interventions to improve population health and health equity.